Improving Sharia Financial Literacy through Financial Education Programs for Youth Organization Activists in Southeast Aceh - Dicky Zulkarnaen; Gundahara; Farma Andiansyah; Bahrul Ilmi (Journal of Community Service and Rural Development, 2025)
This community service program aims to improve sharia financial literacy among Youth Organization Activists in Southeast Aceh. The low understanding of the concept of sharia finance and the high level of consumer behavior are the main backgrounds for the implementation of this program. This activity is carried out through a series of counseling, training, and intensive mentoring that emphasizes the theoretical and practical aspects of sharia-based financial management. The method used in this service is a participatory approach with lecture techniques, interactive discussions, sharia-based financial management simulations, and real case studies. The results of the activity show a significant increase in the Youth's understanding of the concept of sharia finance, as well as an increase in awareness in managing finances more wisely and in accordance with sharia principles. Thus, this program can be a model of sharia financial education that can be applied widely to support more sustainable financial well-being.